Description of the Leadership Style of the Head of the Room and Job Satisfaction of Nurses in the Surgical and Internal Treatment Rooms at Labuang Baji Hospital Makassar - Abdullah, Rusli (Journal of Asian-african Focus in Health, 2023)
Leadership is the most important factor in developing human resources (HR) in an organization. Management styles or leadership styles that are inappropriate or inappropriate for implementation given by leaders to their employees can reduce motivation, performance and ultimately job satisfaction. The aim of the research was to determine the description of the leadership style of the head of the room and the job satisfaction of nurses in the Internal Care and Surgery Room at Labuang Baji Hospital, Makassar . This research is observational research with a descriptive approach . The population in this study were 50 nurses who worked in the Internal Care and Surgical Rooms at Labuang Baji Hospital, Makassar . Total The sample studied consisted of 44 respondents using proportional random sampling technique . Data collection started from March 31 to April 14 2015 using a questionnaire. Based on the research results, it shows that of the 44 respondents , the majority perceived the head of the room's leadership style to be democratic, namely 32 respondents (72 , 7.2 %) , while based on nurses' job satisfaction, the majority felt satisfied , namely 37 people (84.09%) . Based on the research results, it was concluded that the majority of respondents perceived the leadership style of the head of the room to be democratic, and the majority of nurses were satisfied with their work . It is recommended that institutions always evaluate the leadership style of room heads and pay attention to the job satisfaction of nurses on duty in each room in order to achieve good work quality.